The Impact of Investment Opportunity Asset, Return on Assets, and Sales Growth on Dividend Policy: Empirical Analysis of Manufacturing Companies Listed in the Indonesian Sharia Stock Index (ISSI) from 2015-2017 - Andini Nurwulandari (International Journal of Islamic Khazanah, 2020)
The consumer goods industry sector has good prospects and has growth opportunities, but not all companies that enter the consumer goods industry share dividends every year. This research is designed to determine the impact of Company Value, Investment Opportunity Collection, Return on Assets, and Sales Growth regarding the dividend strategies of production firms that are publicly traded ISSI from 2015 to 2017. Purposive sampling was used to collect samples and panel data analysis was used to analyze cross-sections of 15 companies and time series data from 2015 to 2017. This study employs a quantitative research design, employing a panel data regression model and Eview 9 as the data processing tool, and validation of the linear regression panel data using the trial Classical Assumption (Multicollinearity, Heteroscedasticity, and Autocorrelation) and Test of Model Feasibility (Adjusted R-Square, and F Test). The Investment Opportunity Set had a negative but negligible impact on the results. In comparison, the variable Return on Assets has a significant beneficial effect. Sales growth has a detrimental but marginal impact on dividend policy. These findings demonstrate that if the company places a greater emphasis on revenue growth, funds would increase even more, compelling management to pay low or no dividends.